2019
DOI: 10.1002/cncr.32340
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 and randomized, placebo‐controlled phase 2 trial of bevacizumab plus dasatinib in patients with recurrent glioblastoma: Alliance/North Central Cancer Treatment Group N0872

Abstract: BACKGROUND: Src signaling is markedly upregulated in patients with invasive glioblastoma (GBM) after the administration of bevacizumab. The Src family kinase inhibitor dasatinib has been found to effectively block bevacizumab-induced glioma invasion in preclinical models, which led to the hypothesis that combining bevacizumab with dasatinib could increase bevacizumab efficacy in patients with recurrent GBM. METHODS: After the completion of the phase 1 component, the phase 2 trial (ClinicalTrials.gov identifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Dasatinib, an oral ATP-competitive multitarget kinase inhibitor, is able to inhibit all members of the SRC kinase family and has been shown to block growth of bevacizumab-induced glioma invasion in xenograft models [ 134 ]. Galains et al, reported the results of the randomized phase II study analyzing the efficacy of bevacizumab in combination with dasatinib vs. bevacizumab alone in rGBM patients [ 107 ]: the addition of dasatinib did not improve 6m-PFS compared to bevacizumab alone (28.9% [95% CI, 19.5%–40.0%] vs. 18.4% [95% CI, 7.7–34.4%]; p = 0.22) with no significant difference in mOS between the two arms (7.3 m vs. 7.7 m; HR 0.96 [95% CI, 0.64–1.43]; p = 0.83). The epidermal growth factor receptor (EGFR) gene is overexpressed in about 40–60% of GBM and its hyperactivation causes an increase in cell migration, proliferation and invasiveness with a reduction of apoptosis [ 136 , 137 ].…”
Section: Summary Of Major Phase II Clinical Trialsmentioning
confidence: 99%
“…Dasatinib, an oral ATP-competitive multitarget kinase inhibitor, is able to inhibit all members of the SRC kinase family and has been shown to block growth of bevacizumab-induced glioma invasion in xenograft models [ 134 ]. Galains et al, reported the results of the randomized phase II study analyzing the efficacy of bevacizumab in combination with dasatinib vs. bevacizumab alone in rGBM patients [ 107 ]: the addition of dasatinib did not improve 6m-PFS compared to bevacizumab alone (28.9% [95% CI, 19.5%–40.0%] vs. 18.4% [95% CI, 7.7–34.4%]; p = 0.22) with no significant difference in mOS between the two arms (7.3 m vs. 7.7 m; HR 0.96 [95% CI, 0.64–1.43]; p = 0.83). The epidermal growth factor receptor (EGFR) gene is overexpressed in about 40–60% of GBM and its hyperactivation causes an increase in cell migration, proliferation and invasiveness with a reduction of apoptosis [ 136 , 137 ].…”
Section: Summary Of Major Phase II Clinical Trialsmentioning
confidence: 99%
“…Evaluation of clinical samples from completed and ongoing clinical trials [ 47 49 ] should be prioritized to determine the contribution of IRS1/2 expression to therapy responsiveness. Additionally, prospective evaluation of the contribution of IRS1/2 overexpression to patient outcomes and tumor aggressiveness in the absence of RTK treatment could further elucidate the mechanistic specificity of these amplifications in patient tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, despite these positive preclinical studies, the phase II clinical trial (NCT00892177) recently reported the failure of co-treatment with dasatinib and bevacizumab in patients with recurrent GBM, showing that the combination of these two drugs did not ameliorate the outcomes of GBM patients as compared with the single treatment with bevacizumab [ 105 ]. In addition, the phase II clinical trial (NCT00423735) reported a lack of activity of dasatinib against recurrent GBM [ 106 , 107 ].…”
Section: Targeting Src In Glioblastomamentioning
confidence: 99%